Adolescent cancer survivors' experiences of supportive care needs: A qualitative content analysis. (14th August 2019) - Valizadeh, Leila; Zamanzadeh, Vahid; Ghahramanian, Akram; Musavi, Saeed; Akbarbegloo, Masoomeh; Chou, Fang‐yu
Abstract: Supportive care is an important strategy that can help cancer survivors manage changes and problems during their follow‐up care. Identifying patients' care needs is one of the primary steps of the nursing process to plan effective nursing interventions. The aim of this study was to explore adolescent cancer survivors' supportive care needs. Purposeful sampling was adopted to select 49 participants from hospitals to participate in face‐to‐face, semistructured interviews. The qualitative content analysis method was conducted for data analysis. Ten subcategories and four main categories – empathetic care, information about survival period, instrumental support, and cooperation in care – were extracted from the data. These four categories formed a major theme, "supportive care", as the primary healthcare need. This study highlights that supportive care should be developed collaboratively by family and healthcare providers to meet the needs of adolescent cancer survivors. Survivors' strengths and limitations should be identified, and then supportive care can be provided, such as giving appropriate information, enabling survivors to access supportive networks, and improving survivors' confidence and autonomy with their self‐management.